Monitoring and sensing of (HF)n linear chain for n = 1–4 on aluminum nitride nanocage in both gas and water phases; computational study. Issue 4 (August 2021) - Fang, Yu; Li, Huahui; Guo, Xingchen; Li, Mengting; Liu, Peng
Abstract: The interaction as well as the adsorption behavior of an (HF)n linear chain for n = 1–4 was inspected on an AlN nanocage using ab initio calculations to understand the ability of this material to monitor and sense the (HF)n in gas and water phases. The adsorption energies, optimized configurations, charge transfer, and the work function for this gas were calculated on the AlN nanocage surface. Also, the effect of the HF linear chain size was investigated on the adsorption energy and all of the electronic properties. According to the adsorption energy, the most stable configuration for the (HF)n on the AlN nanocage surface is the dimer form of the HF gas. Also, after the adsorption of the (HF)n on the AlN nanocage, the HOMO-LUMO gap decreased dramatically from 3.99 to 3.36 eV, leading to an increase in conductivity. Furthermore, the AlN nanocage can sense the (HF)n in the presence of many environmental pollutants. Graphical Abstract: ga1 Highlights: Adsorption of (HF)n cluster on the AlN nanocage surface were studied. The Eg gap of the AlN nanocage decreased significantly after adsorption of (HF)n. The AlN nanocage can be used as a promising nanomaterial for detection of (HF)n .